An art district system dynamics model of diversified operation based on game theory. (19th May 2018) - Bai, Ruiliang; Zhang, Mingyu
Abstract: An evolutionary game model of the mixed strategy of diversified operation of the main galleries and restaurants in the art district is established, and four special equilibriums and one general equilibrium are obtained by formula derivation, and the simulation is carried out through the System Dynamics. The condition and possibility of achieving equilibrium are analyzed.